2007
DOI: 10.1177/095632020701800301
|View full text |Cite|
|
Sign up to set email alerts
|

Los Alamos Hepatitis C Virus Sequence and Human Immunology Databases: An Expanding Resource for Antiviral Research

Abstract: The hepatitis C virus (HCV) resource at Los Alamos (hcv.lanl.gov) provides access to multiple databases: one containing annotated sequences and the other a repository of immunogenic epitopes. They are derived from databases originally developed for HIV research (hiv.lanl.gov). HCV and HIV are RNA viruses with relatively compact genomes (around 10 kb) that are extraordinarily variable, both within and between hosts. This diversity requires methods to track and exclude variants from an individual infection or fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…A previous study in 1997 [40] reported that subtype 1b was the most prevalent subtype (76%), followed by subtype 3a (19%) and single cases of subtypes 1a and 2a, which suggests that the prevalence of subtype 3a has increased and that fewer subtype 1b strains are now circulating. Subtypes 1b and 3a are also dominant over other subtypes in Russia, Estonia and western Europe [41]. While both subtypes have a similar prevalence (45%) in Russia, the relative prevalence of subtype 1b over subtype 3a is three‐fold greater in Estonia (71% vs. 24%; [30]) and 6.5‐fold higher in western Europe (58% vs. 9%).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study in 1997 [40] reported that subtype 1b was the most prevalent subtype (76%), followed by subtype 3a (19%) and single cases of subtypes 1a and 2a, which suggests that the prevalence of subtype 3a has increased and that fewer subtype 1b strains are now circulating. Subtypes 1b and 3a are also dominant over other subtypes in Russia, Estonia and western Europe [41]. While both subtypes have a similar prevalence (45%) in Russia, the relative prevalence of subtype 1b over subtype 3a is three‐fold greater in Estonia (71% vs. 24%; [30]) and 6.5‐fold higher in western Europe (58% vs. 9%).…”
Section: Resultsmentioning
confidence: 99%
“…In the two cases where mutations did occur, these were novel mutations not found in sequence databases (Combet et al , 2007; Hraber et al , 2007) and both were associated with a functional impact on T-cell recognition. In the absence of the infecting strain, it is not possible to prove that the mutations occurred within the donors.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 82 Brazilian sequences belonging to subtype 1a and 161 sequences of subtype 1b were obtained with the in silico search of Brazilian HCV polymerase fragment sequences on Los Alamos HCV database (https://hcv.lanl.gov/content/index) and Genbank (https://www.ncbi.nlm.nih.gov/genbank/). Datasets of subtypes 1a and 1b with in silico and target sequences obtained on that work were used to obtain a more detailed genetic reconstruction analysis with local geographical information.…”
Section: Methodsmentioning
confidence: 99%